Flotation of Platinum Group Elements Ores: A Review. (17th February 2023) - Sahu, P.; Dash, P.; Jena, M. S.; Mandre, N. R.
ABSTRACT: The unique physical and chemical properties of platinum group elements are making them indispensable in many modern industrial applications. Platinum-group minerals are usually beneficiated by flotation or gravity separation followed by flotation. Due to poor liberation characteristics and interstitial attachment of these minerals with base metal sulfides, chromites, and silicates, fine grinding is necessitated. Significant variability of platinum group element deposit types and their mineralogical characteristics create a challenge to choose a proper reagent suite. The present article critically discusses all the factors that affect the flotation of platinum group element bearing minerals, flotation routes, essential gaps, the problems associated with their processing, and suitable reagent suites used in different ore deposits and plant practices.